STRATEGI PENGEMBANGAN PENGELOLAAN PARIWISATA AIR TERJUN WERA SALUOPA DI KABUPATEN POSO - Abidjulu, Rinto Z W (Katalogis, 2015)
This study aims to formulate a development strategy of tourism management of Saluopa Water Fall in Poso. This research was conducted in the village of Wera Pamona Puselemba in Poso Regency. The data were collected through direct interview with the key informants and observations. The data is then analyzed by SWOT analysis. The results show that the highest of strenght factor is the object of the waterfall itself with a score of 0.7. While, the potential of natural resources of flora and fauna have not been optimally utilized with a score of 0.696667. It is categorised as the highest of weakness factor. In addition, the waterfall is located close to the cocoa plantations so that it is an opportunity for developing agro-tourism package and it may employee the local people. The score for this opportunity is 0.926829. However, the security issue is the highest threat of Wera Saluopa waterfall management. The reason for this is that the area has still been affected by the trauma of social conflict with a score of 0.893023. The results of SWOT analysis strategy show that the development of Wera Saluopa management is a strategy that supports the aggressive growth. Therefore, the potential attractions around the waterfall area and the utilization of cacao plantations should be maintained and preserved because the area can developed as agro-tourism package and has conomic value added for local communities.